Agreement of Anterior Segment Parameter Measurements With CASIA 2 and IOLMaster 700 - Ruan, Xiaoting; Yang, GuangYao; Xia, Zhaoxia; Zhang, Jiaqing; Gu, Xiaoxun; Tan, Yuan; Liu, Zhenzhen; Luo, Lixia (Frontiers in Medicine, 2022)
Purpose To compare the difference and agreement in central corneal thickness (CCT), keratometry (K), anterior chamber depth (ACD), aqueous depth (AQD), and lens thickness (LT) measured with CASIA 2 and IOLMaster 700 in patients with cataract. Methods A total of 81 patients with cataract (81 eyes) scheduled for phacoemulsification were prospectively collected from March to May, 2020 in the cataract department of Zhongshan Ophthalmic Center, Sun Yat-sen University, including 43 males and 38 females with age of 61.5 ± 10.6 years. CCT, anterior Kf, anterior Ks, real Kf, real Ks, ACD, AQD, and LT were measured with CASIA 2 and IOLMaster 700. Paired t-test, intraclass correlation coefficients (ICCs), 95% limit of agreement (95% LoA), and Bland-Altman plots were performed and used to analyze the difference and agreement between the two devices. Results There was no statistically significant difference in anterior K measurement with the CASIA 2 (44.3 ± 1.66 mm) and IOLMaster 700 (44.31 ± 1.67 mm, P = 0.483). Differences among the CCT, anterior Kf, real Kf, real Ks, ACD, AQD, and LT measured by the two instruments were statistically significant (P < 0.001). The ICCs of CCT, anterior Kf, anterior Ks, real Kf, real Ks, ACD, AQD, and LT measurements between the two devices were 0.892, 0.991, 0.991, 0.827, 0.817, 0.937, 0.926, and 0.997, respectively. The 95% LoA between CASIA 2 and IOLMaster 700 was −30.06 to 0.43 μm for CCT, −0.3 to 0.48 D for anterior Kf, −0.46 to −0.43 D for anterior Ks, −1.49 to −0.49 D for real Kf, −1.62 to −0.49 D for Real Ks, −0.03 to 0.24 mm for ACD, 0.04 to 0.25 mm for AQD, and −0.06 to 0.09 mm for LT. Conclusion Anterior Kf, anterior Ks, ACD, AQD, and LT have excellent agreement between the two devices. CCT, real Kf, and real Ks have moderate agreement between the two devices. It is recommended to use anterior Kf, anterior Ks, ACD, AQD, and LT interchangeably between CASIA 2 and IOLMaster 700.